Profiling of Collagens from Swim Bladder of Catfish (Pangasius sp.) by Acid Extraction - Gressty Sari Br Sitepu; Joko Santoso; Wini Trilaksani (Jurnal Pengolahan Hasil Perikanan Indonesia, 2019)
Swim bladders of catfish contain high protein, therefore it is can be used as a raw material for collagen. The study aims to determine the chemical characteristics of swim bladders, the pretreatment of non-collagen, extraction of collagen dissolves acid and to evaluate the characteristics of collagen. The method of this study is KOH pretreatment with a concentration of 0,05; 0,1; and 0,15 for 12 hours. The extraction process is done by soaking the sample in a solution of acetic acid with a concentration of 0,25; 0,5 and 0,75 M (ratio 1:10; b/v) and extraction time for 24; 48; and 72 hours at 4oC. The experimental design used for alkaline and acetic acid pretreatment were factorial completely randomized design. The result showed that the protein content of swim bladder was 85,26% (db), the profile of amino acids were dominated by three amino acids namely glycine (56,85 mg/g), prolyne (31,03 mg/g), and alanyne (23,85 mg/g). Using 0,05 M KOH for 8 h was selected as the best pretreatment method for collagen extraction. Extraction method using 0,50 M acetic for 48 h resulted he best collagen which revealed the existence of a triple helix structure and had Tg 84oC.